2017
DOI: 10.18311/gjeis/2017/15617
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Motivations as Mediator of Big Five Personality and Knowledge Sharing

Abstract: The purpose of this research is to examine the interrelationships among various interpersonal psychological factors to explain their effect on knowledge sharing behaviors at workplace. A sample of 450 employees was drawn from knowledge based industries. To tap the information regarding performance on knowledge sharing, Big Five personality, and motivation, Knowledge Sharing Behavior (KSB) scale by Yi (2009)62, Big Five personality traits scale by Gosling et. al. (2003)27, extrinsic and intrinsic motivation sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The requester's convincingness in such cases can be based on the requester's reputation as a loyal and committed employee herself (Agostini & Nosella, 2016). Balance of intrinsic and extrinsic motivation in the holder's motivation structure: a share of intrinsic motivation, for example, based on strive for professional excellence or for individual or organizational societal impact, can be positively related to the holder's eagerness to share sensitive knowledge (Andreeva & Sergeeva, 2016; Lee et al, 2015; Rajput & Talan, 2017). Traits related to the so‐called “cultural dimensions” based on the ideas of Hofstede (1980) and Trompenaars (1994) further developed in House, Hanges, Javidan, Dorfman, and Gupta (2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requester's convincingness in such cases can be based on the requester's reputation as a loyal and committed employee herself (Agostini & Nosella, 2016). Balance of intrinsic and extrinsic motivation in the holder's motivation structure: a share of intrinsic motivation, for example, based on strive for professional excellence or for individual or organizational societal impact, can be positively related to the holder's eagerness to share sensitive knowledge (Andreeva & Sergeeva, 2016; Lee et al, 2015; Rajput & Talan, 2017). Traits related to the so‐called “cultural dimensions” based on the ideas of Hofstede (1980) and Trompenaars (1994) further developed in House, Hanges, Javidan, Dorfman, and Gupta (2004).…”
Section: Discussionmentioning
confidence: 99%
“…The “lack of motivation to knowledge sharing as activity not included into regular job duties” construct has been transformed into such more specific barrier formulations as “lack of material remuneration for knowledge sharing” and “lack of immaterial remuneration for knowledge sharing.” Studies of both remuneration types influence on knowledge sharing are widespread in knowledge management literature from the classical works like (Husted & Michailova, 2002; Kogut & Zander, 1992) to newer (Andreeva & Sergeeva, 2016; Lee, Reinicke, Sarkar, & Anderson, 2015; Rajput & Talan, 2017); so it is interesting to look on lack of remuneration of both types as on knowledge sharing barriers in the specific industrial context of the current research project.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some factors, such as financial or other benefits, applaud and praise good work. Perks and privileges also play a great role in attaining external motivation [35]. Motivation (intrinsic, extrinsic) is the mediator for someone to perform an action.…”
Section: Mediating Role Of Motivationmentioning
confidence: 99%
“…External factors of extrinsic motivation such as praise, bonuses, rewards, and others play a key role in achieving extrinsic motivation. For example, in order to derive the potential results at the workplace, the managers and/or supervisors provide a decent evaluation of subordinates' work which is often less relegated through extrinsic motivation (Rajput & Talan, 2017). Extrinsic motivation can build the basis for intrinsic motivation and without achieving intrinsic motivation the work environment remains subdued and/or loses track of work.…”
Section: Motivationmentioning
confidence: 99%
“…From the existing literature, we found that motivation also plays a role of mediation among different variables. Rajput and Talan (2017) conducted a study in which motivation plays a mediation role among knowledge sharing behavior and big five personality traits. Motivation has been argued as a good mediator of management styles and worker's engagement.…”
Section: Motivation As a Mediatormentioning
confidence: 99%